Analisis manajemen waktu menggunakan metode CPM (Critichal Path Metodh) pada proyek pembangunan Poliklinik Terpadu RSUD Prof. Dr. Soekandar Mojosari - Qordhowi, Andrian Firdaus Yusuf Al; Kurniawan, Moch Wahyu (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The development of health infrastructure that has great value must be accompanied by good time management. Each project has a work duration milestone. One way that a project can be said to be successful is that it has achieved accuracy in its work time. The aim of this research is to identify the duration of work on the integrated polyclinic development project at RSUD dr. Soekandar-Mojosari by determining the critical path obtained which will later produce dependency relationships between jobs and understand rescheduling and find critical paths on jobs. This research was carried out on the integrated polyclinic construction project at RSUD Prof. Dr. Soekandar-Mojosari, East Java. This project has a work duration of 210 days with a value of Rp. 33. 936,829,000,-. Time management analysis is obtained using the CPM (Critical Path Method) method by determining the work network and will later produce the number of existing critical paths. The duration obtained from analysis using the CPM method will then be crashed to determine the best time to complete a job. With critical work, the project implementer will determine work that cannot be postponed. From the research results, the duration obtained for roof floor structure work items is 35 working days to 28 working days and there are 12 critical work items.